2016
DOI: 10.1080/15374416.2016.1178124
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations Between Binge Eating and Psychological Risk Factors in Adolescence

Abstract: There is evidence that intrapersonal psychological factors might contribute to the development of binge eating. However, studies considering reciprocal effects between risk factors and disordered eating are rare. The present article investigates the nature of the temporal relationships between binge eating and low self-esteem, depressive symptoms, interoceptive deficits, perfectionism, weight/shape concerns, dietary restraint, and the internalization of the societal body ideal in adolescence while taking into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 88 publications
0
17
0
1
Order By: Relevance
“…In their meta-analysis, Puccio et al (2016) found that the effect of DE on depression and vice versa was differentially moderated by different operationalizations of DE; for example, the effect of DE on depression was stronger for overall DE symptoms relative to bulimic and binge-eating symptoms. By contrast, other recent studies have suggested either a unidirectional longitudinal association where binge-eating symptoms predicted depression (Sehm & Warschburger, 2016) or a nonsignificant relationship between dysfunctional food consumption or dieting with depression (De Caro & Di Blas, 2016). Thus, the longitudinal DE-depression relationship might be subserved by specific symptoms of DE or, at the very least, that distinct symptoms of DE confer increased risk for developing depression and vice versa.…”
Section: Disordered Eating and Depressionmentioning
confidence: 88%
“…In their meta-analysis, Puccio et al (2016) found that the effect of DE on depression and vice versa was differentially moderated by different operationalizations of DE; for example, the effect of DE on depression was stronger for overall DE symptoms relative to bulimic and binge-eating symptoms. By contrast, other recent studies have suggested either a unidirectional longitudinal association where binge-eating symptoms predicted depression (Sehm & Warschburger, 2016) or a nonsignificant relationship between dysfunctional food consumption or dieting with depression (De Caro & Di Blas, 2016). Thus, the longitudinal DE-depression relationship might be subserved by specific symptoms of DE or, at the very least, that distinct symptoms of DE confer increased risk for developing depression and vice versa.…”
Section: Disordered Eating and Depressionmentioning
confidence: 88%
“…Several risk factors for ED pathology are well‐established and similar to those of clinically diagnosed EDs, including female gender, body mass index, sociocultural pressure to be thin, body dissatisfaction, problems in interpersonal relationships, and internalizing problems (Culbert, Racine, & Klump, 2015; Jacobi et al, 2004; Krug et al, 2013; Lavender, De Young, & Anderson, 2010; Marmorstein, von Ranson, Iacono, & Malone, 2008; Sehm & Warschburger, 2018; Smith et al, 2018; Stice, 2002). Personality traits—specifically neuroticism—are also associated with ED pathology (Keel & Forney, 2013; Levallius, Clinton, Bäckström, & Norring, 2015; Lilenfeld, Wonderlich, Riso, Crosby, & Mitchell, 2006), suggesting that other personality traits that are related to neuroticism and internalizing problems, such as rejection and justice sensitivity (Schmitt, Gollwitzer, Maes, & Arbach, 2005), may be associated with ED pathology as well.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the presence of other psychiatric symptoms prior to ED onset is unsurprising given the high rates of lifetime comorbidity associated with EDs [5]. However, as the studies reviewed here and those outside the scope of this review have demonstrated, there is mixed evidence for any prospective association between affective and ED symptoms/disorders [74][75][76]. Further longitudinal research with frequent assessment points is warranted in order to tease apart any chronological patterns in the appearance of ED and other psychiatric disorder-related symptomatology or understand how they collectively contribute to the onset of EDs.…”
Section: Discussionmentioning
confidence: 84%